Unveiling the chemotherapeutic potential of two platinum(IV) complexes in skin cancer: in vitro and in vivo Insights - Amjad Slika; Christina Haydar; Joelle Bou Chacra; Seba Al Alam; Stephanie Mehanna; Anthony Lteif; Maria George Elias; Krishant M. Deo; Robin I. Taleb; Janice R. Aldrich-Wright; Costantine F. Daher (Current Research in Pharmacology and Drug Discovery)
The present study investigates the chemotherapeutic potential of two platinum (IV) complexes, P-PENT and P-HEX, against skin cancer in vitro and in vivo. Both complexes exhibited potent cytotoxicity against HaCaT-II-4 cells with IC50 values of 0.8 ± 0.08 μM and 1.3 ± 0.16 μM respectively, while demonstrating 8-10-fold selectivity compared to mesenchymal stem cells (MSCs). Western blot analysis revealed significant modulation of key apoptotic and survival pathways, including upregulation of Bax/Bcl2 ratio, cleaved caspase 3, and cytochrome c, suggesting induction of intrinsic apoptosis. The complexes also inhibited PI3K and MAPK pathways, as evidenced by decreased p-AKT/AKT and p-ERK/ERK ratios. Flow cytometry confirmed significant apoptotic cell death. Both complexes also increased reactive oxygen species production. In a DMBA/TPA-induced skin carcinogenesis mouse model, both complexes significantly suppressed tumor growth at doses considerably lower than the maximum tolerated dose, with no detectable toxicity. A dose escalation study in BALB/c mice showed that P-PENT and P-HEX were approximately 5-fold and 4-fold more tolerated than cisplatin, respectively. In conclusion, the present study provides evidence that P-PENT and P-HEX may have the characteristics of an effective and potentially safe anti-tumor drug that could be used in skin cancer treatment.